EU as a Highly Competitive Social Market Economy –Goal, Options, and Reality - Václav Šmejkal; Stanislav Šaroch (Review of Economic Perspectives, 2015)
In paragraph 3 of its Article 3, the Treaty on European Union (TEU) requires the EU to go after the goal of a highly competitive social market economy for the first time. It is noticeable in the aforementioned Treaty clause that although it deals with the EU internal market, its authors burdened it with a mission that is far more socially-oriented than market-oriented. However, is ,,a highly competitive social market econo-my“ of today a meaningful goal and does the EU in its present form have the project and powers to achieve such an objective? The paper is a combination of economic and legal -political analysis through which the authors try to answer three main questions: What is the contemporary meaning of the term “social market economy” in the both economic and EU-law academic theory? Can the EU within the powers conferred to it positively fulfill such an objective, or can it just approach it by weakening the still pre-vailing tendency towards liberalization and deregulation brought about by the construc-tion of the EU internal market and by the promotion of its freedoms?
Keywords: 330